Cellular apoptosis susceptibility (CAS) is linked to integrin β1 and required for tumor cell migration and invasion in hepatocellular carcinoma (HCC) - Winkler, Juliane; Rössler, Stephanie; Sticht, Carsten; Drucker, Elisabeth; Holzer, Kerstin; Eiteneuer, Eva; Herpel, Esther; Breuhahn, Kai; Gretz, Norbert; Schirmacher, Peter; Singer, Stephan (OncoTarget, 2016)
Importins and exportins represent an integral part of the nucleocytoplasmic transport machinery with fundamental importance for eukaryotic cell function. A variety of malignancies including hepatocellular carcinoma (HCC) show de-regulation of nuclear transport factors such as overexpression of the exportin Cellular Apoptosis Susceptibility (CAS). The functional implications of CAS in hepatocarcinogenesis remain, however, poorly understood. Here we integrated proteomics, transcriptomics and functional assays with patient data to further characterize the role of CAS in HCC. By analyzing ~ 1700 proteins using quantitative mass spectrometry in HCC cells we found that CAS depletion by RNAi leads to de-regulation of integrins, particularly down-regulation of integrin β1. Consistent with this finding, CAS knockdown resulted in substantially reduced migration and invasion of HCC cell lines as analyzed by 2D ‘scratch’ and invasion chamber assays, respectively. Supporting the potential in vivo relevance, high expression levels of CAS in HCC tissue samples were associated with macroangioinvasion and poorer patient outcome. Our data suggest a previously unanticipated link between CAS and integrin signaling which correlates with an aggressive HCC phenotype.
Gesehen am 23.04.2019